2016
DOI: 10.1007/s11104-016-2906-1
|View full text |Cite
|
Sign up to set email alerts
|

The limiting roles of nitrogen and moisture on Sphagnum angustifolium growth over a depth to water table gradient

Abstract: Background and aims Boreal peatlands are projected to face numerous stressors in the future, including changes in precipitation and nitrogen cycle perturbations. Nitrogen is currently believed to be the limiting factor to peatlands of western Canada, including to Sphagnum, however new insights suggest the possibility of multiple limiting factors. Methods Growth, nitrogen assimilation, and annual retention of Sphagnum angustifolium, a species with a broad niche, were observed across a depth to water table gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Grassland formation explained the second largest variation for ANPP, BNPP, and TNPP (Figure 4). The possible key mechanisms underlying these patterns could be as follows: (a) soil is the direct medium for plant root growth; thus, soil environmental conditions will inevitably exert significant impacts on root growth and biomass allocation (Bardgett et al., 2014; Graham & Vitt, 2016); (b) there is confirmed evidence that topography can affect plant growth by modifying water, heat and their distributions (Chen et al., 2013; Xie et al., 2018); and (c) grassland formation was the primary determinant of root turnover in grasslands as found in a previous study (J. Wang et al., 2019). Overall, our results underscore an urgent need to incorporate multidimensional driving factors into the estimation of grassland productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grassland formation explained the second largest variation for ANPP, BNPP, and TNPP (Figure 4). The possible key mechanisms underlying these patterns could be as follows: (a) soil is the direct medium for plant root growth; thus, soil environmental conditions will inevitably exert significant impacts on root growth and biomass allocation (Bardgett et al., 2014; Graham & Vitt, 2016); (b) there is confirmed evidence that topography can affect plant growth by modifying water, heat and their distributions (Chen et al., 2013; Xie et al., 2018); and (c) grassland formation was the primary determinant of root turnover in grasslands as found in a previous study (J. Wang et al., 2019). Overall, our results underscore an urgent need to incorporate multidimensional driving factors into the estimation of grassland productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Grassland formation explained the second largest variation for ANPP, BNPP, and TNPP (Figure 4). The possible key mechanisms underlying these patterns could be as follows: (a) soil is the direct medium for plant root growth; thus, soil environmental conditions will inevitably exert significant impacts on root growth and biomass allocation (Bardgett et al, 2014;Graham & Vitt, 2016); (b) there is confirmed evidence that topography can affect plant a Top 10 countries in terms of grassland area. The area of each grassland formation or region is derived from distribution mapping of global grasslands (Dixon et al, 2014).…”
Section: Spatial Patterns and Driving Mechanisms Of Above-and Belowgr...mentioning
confidence: 99%
“…Actual load may be considerably higher than estimated because of additional mire water storage in basal snow layers, which is quite common in microrelief depressions (Eurola, 1975). Thus, known from the literature concepts "permanent bends of the main stem" (Rochefort et al, 1990), "innate seasonal markers" (Jauchiainen et al, 1997); "kinks" (Camill et al, 2001), "snow weighted crooks" (Vitt, 2007), "growth markers created by snowpack conditions" (Turetsky et al, 2008) and "innate snow-bend markers" (Graham & Vitt, 2016) are consistent with nival geotropic curvatures.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown how Sphagnum length increment changes between years (e.g. Moore 1989, Graham and Vitt 2016. In our 8-year study, large inter-year variation of LI of a lawn-hollow species (S. fallax) and species with a wide ecological niche (S. angustifolium, S. magellanicum) was linked to weather uctuations.…”
Section: Trait-and Species-speci C Response Of Sphagnum To Weather Fa...mentioning
confidence: 56%